On a Theoretical Analysis of the Family and Economic Growth - ODEDOYIN, Stephen Olabode (Journal of Mathematical Economics and Finance; Vol 5 No 2 (2019): JMEF, Volume V, Issue 2 Winter 2019, 2019)
The paper considers the prospects of constructing theoretical postulates on the family that is consistent with some of the main features of economic growth. Theoretical abstraction of the parameters involved based on the intergenerational dynastic model is analyzed and compared to evidence. Descriptive and analytical technique were employed in analyzing the model. Nonmarket productivity levels and their effect on initial human capital endowment of households were also considered.